مفهوم اليقين عند الإمام فخر الدين الرازي في تفسيره "مفاتيح الغيب" : دراسة تحليلية - شمس البحر (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study brings to light the life of Imam Fakhr al-Din Muhammad ibn 'Umar al-Razi (born 544 A.H./1149 C.E.; died 606 A.H./1210 C.E.) focusing on his concept of certainty (yaqin) with reference to his exegetical work Mafatil al-Ghayb. It aims to expose the interpretive method in elucidating the meaning of certainty (yaqin). The significance of this study is obvious, when it becomes clear that certainty has always been the subject of scholarly discussion among the Mutakallimin (due to its relation to the sources of knowledge concerning the major principles of religion such as the concept of divinity, Propethood (nubuwwah) and afterlife (akhirah), as well as among the Jurists and Ululiyyin (since they consider yaqin to be of great importance in defining the sources of shari'ah rules), just as the Sufis make it as the basis of their method of taÎawwuf. In pursuit of its objective, this study uses both inductive and analytical methods in describing his biography and views and in explicating the various contexts of the term yaqin and its derivatives, cognates and contraries. The study concludes with three findings: (i) although he gives more than one definition of yaqin, Imam al-Razi consistently holds that certainty is a cognitive state of mind resulting from the removal of doubt due to the presence of abundant evidence based on objective facts, empirical data and valid reasoning, all of which lead to true knowledge about reality; (ii) on Imam al-Razi's view, certainty (yaqin) becomes the foundation upon which one must build his/her faith (iman) and personal knowledge (ma'rifah) in relation to Allah and Propethood of His Messenger; (iii) the study shows that Imam al-Razi is not rationalist in toto, since he does as a matter of fact refer to traditional authorities and still follows the standard method of tafsir al-Qur'an bi al-Qur'an, while at the same time citing the Prophet's hadith and the sayings of His Companions (aqwal al-Sahabah) and the early scholars (al-salaf al-Salih) in support of his interpretation throughout his tafsir work, Mafatih al-Ghayb.